Image repair theory: framing of Israel by gov.il media in the Gaza conflict - Darwis, Yuliandre; Wafi, Fadhlil; Maulana, Ridho (Jurnal Studi Komunikasi, 2025)
The conflict between Israel and Hamas in Gaza is highly complex. The initial attack by Hamas on October 7, 2023, followed by Israel’s counterattack, captured significant international attention. However, numerous accusations have been directed at Israel, which is increasingly perceived as an actor in the escalation of the conflict. This study aimed to examine how Israel, through its official media platform Gov.il, engages in media framing with the purpose of image restoration. The data in this study were collected by analysing 17 news articles published on the Gov.il website using the keywords ‘“Israel image repair Gaza’, ” ‘“Hasbara communication Gaza,’,” ‘“IDF and civilians Gaza’, ” ‘“Gov.il narrative framing’, ” and ‘“Genocide accusation response’” from October 7, 2023, to August 30, 2024. This study applies the data analysis method of Miles and Huberman to address the research questions. The findings highlight two key points: Israel’s image restoration strategy in Gov.il media uses (1) a reduced offensiveness approach, specifically through the variants of bolstering and differentiation, and (2) evasion of responsibility through the variant of defensibility. This study also aimed to identify Israel’s image restoration strategies in repairing and maintaining its reputation before the international community, especially regarding Israel being accused of committing acts of genocide in Gaza by the international community and countries in the world in the 2023 Israel-Palestine conflict. This research uses a qualitative method by collecting news articles from Gov.il media using the keyword "Gaza’" and analysing them to obtain patterns of Israel’s image restoration strategies in the media. The results show that the framing of news about Israel is positive by showing that Israel has good initiatives toward civilian victims and that Israel is a country that prioritises humanitarian actions. Furthermore, this study also proves that the pattern of Israel’s image restoration tends to use the strategy of reducing forgiveness, especially using bolstering techniques, namely strengthening the positive feelings of the audience, compensation, reducing attack, differentiation, distinguishing their actions from other actions, and attacking the counterattacking the accuser.